"Another nice mess you've gotten me into" employers' liability for workplace banter. Issue 6 (13th November 2017) - Middlemiss, Sam
Abstract : Purpose: Banter has been defined in the Oxford Dictionary as "the playful and friendly exchange of playful remarks" [www.merriam-webster.com/dictionary/banter ]. This suggests that it is a form of dialogue or conversation that is welcome, non-threatening and appreciated by the recipient. However, this is often not the case, and the purpose of this paper is to consider the legal rules dealing with banter where it is threatening, unwanted or oppressive to the recipient. Where there is a discriminatory aspect to the banter, the protection provided under equality law will be considered. Banter can be directed at workers with different characteristics (e.g. disability, age, religion, sex, race or sexual orientation), and this paper will consider discriminatory banter whatever the basis. The different types of dialogues falling under the term banter will be analysed and the extent to which legal protection is in place to deal with it will be considered. The statutory legal rules dealing with harassment and bullying in the UK are the most relevant to controlling workplace banter and accordingly will be given primary consideration. Finally, recommendations will be made for improving both management practice and the law in this area. Design/methodology/approach: The methodology used is a thorough review of secondary sources in the UK including relevant statutes and legal cases and research undertaken in this area. Findings: There is a need for legislative change to protect victims of unwanted workplace banter. Research limitations/implications: Legal and managerial solutions to a complex problem. Practical implications: Very few sources of primary research. Originality/value: Highly original.